PENINGKATAN INTERAKSI BELAJAR MATEMATIKA MATERI TRIGONOMETRI MELALUI METODE QUANTUM LEARNING PADA SISWA KELAS X.2 SMA DDI MAROS - A. Muhajir Nasir; Syamsuriawati Syamsuriawati (Universitas Cokroaminoto Palopo, 2021)
This study aims to increase the interaction of learning mathematics with trigonometry through the use of the Quantum Learning method in class X.2 SMA DDI Maros. This type of research is Classroom Action Research using the Kemmis and Mc Taggart cycle model. The subjects of this study were students of class X.2 SMA DDI Maros for the academic year 2020/2021. This classroom action research was carried out in 2 cycles. Data collection techniques using observation and tests. The data analysis used is descriptive qualitative and descriptive quantitative. The method used in this study is the Quantum Learning learning method with the research success criteria the percentage of student learning interactions reaches 75%. The results of the study indicate that the Quantum Learning method can improve the learning interactions of class X.2 students of SMA DDI Maros. The learning is using the TANDUR strategy in the form of facilities from the teacher so that students can grow the strength of AMBAK, get learning experiences, name materials, demonstrate results, repeat material, and celebrate success. In the pre-action or initial score, the average student learning interaction in mathematics obtained a percentage of 74.91%. After being given the action, it increased to 78.47% at the end of the first cycle, and at the end of the second cycle, it increased to 87.78%.